IMPACT OF FARMER FIELD SCHOOLS ON SOCIAL WELLBEING OF FARMING COMMUNITY IN KHYBER PAKHTUNKHWA, PAKISTAN - S. Muhammad; K. M. Chaudhry; A. Khatam; I. Ashraf (Journal of Animal and Plant Sciences, 2013)
The paper focuses on the impact of farmer field schools (FFS) on social wellbeing of farming community. For this purpose, six districts from the central region of Khyber Pakhtunkhwa including Peshawar, Charsadda, Nowshera, Mardan, Swabi and Kohat were selected. Data were collected on various aspects of social wellbeing of farming community from 240 randomly selected FFS farmers and 60 extension field staff respondents. The data were analyzed using a paired t-test for comparison of pre and post FFS scenarios. The results show that decision making was ranked 1st with mean values 3.38, 3.94 closely followed by confidence building and spirit of self help which were ranked 2nd and 3rd with mean values 3.41, 3.94 and 3.40, 3.92 in pre and post-FFS scenarios, respectively. Similarly, field staff respondents ranked spirit of self help by farmers as 1st with mean values 3.31, 4.04, decision making as 2nd with mean values 3.27, 3.91, and confidence building as 3rd with mean values3.39 and 3.97 in pre and post-FFS scenarios, respectively. This situation shows a highly significant difference between the pre and post FFS scenarios. Hence, it can be concluded fromthe study that FFS had a significant impact on all aspects of social wellbeing of farming community as a result of various project activities.
Keywords: Extension approaches; Impact of Farmer Field School; Social wellbeing